Representation of the Concept “Joy” in Proverbs and Sayings: Cultural and Value Accents - Tajenova, Sayora Bayronovna (TLEP – International Journal of Multidiscipline, 2025)
This article examines the representation of the concept “joy” in proverbs and sayings across different cultures, focusing on their linguistic, cultural, and value dimensions. Proverbs serve as concise carriers of collective wisdom, reflecting the emotional, moral, and philosophical worldviews of nations. The research investigates how the concept of joy is expressed in English, Uzbek, and Russian proverbs, identifying universal and culturally specific aspects of its meaning. Using a linguocultural and comparative approach, the study reveals that in English proverbs, joy is linked with optimism, personal effort, and gratitude; in Uzbek proverbs, it is associated with collective harmony, spirituality, and shared happiness; while in Russian proverbs, joy is viewed through the prism of endurance, modesty, and moral reflection. The analysis demonstrates that joy functions not only as an emotion but also as a moral value, uniting people through common human feelings while highlighting unique national identities. The study concludes that understanding the cultural and value accents of joy enriches cross-cultural communication and deepens insight into the emotional and ethical nature of language.